Reordering Ranganathan: Shifting User Behaviours, Shifting Priorities - Connaway, Lynn Silipigni; Faniel, Ixchel M. (Journal of Information and Knowledge, 2015)
S.R. Ranganathan's Five Laws of Library Science provide a broad framework for designing and evaluating library programmes, activities and services. The laws continue to be extensively cited even today suggesting their continued relevance. This paper attempts to interpret the five laws in the present day context of information abundance, digital revolution, currently available resources and services, and user behaviours. The idea has been to suggest how libraries and librarians can better connect to those behaviours. After examining the changing roles of the Five Laws on the basis of findings of recent research, the paper suggests reordering and reframing of the Five Laws of Library Science. A number of recommendations for realizing the intent of the laws have also been made.